Dupilumab modulates specific IgE mite responses at the molecular level in severe T2-high atopic dermatitis: A real-world experience - González-Pérez, Ruperto; Poza-Guedes, Paloma; Mederos-Luis, Elena; Sánchez-Machín, Inmaculada (Frontiers in Medicine, 2022)
Background: Dupilumab, a fully human monoclonal antibody to IL-4Rα that inhibits both IL-4 and IL-13 signaling, has previously shown a marked and rapid improvement when treating the moderate-to-severe forms of AD. We sought to evaluate the real-world evidence of dupilumab in the modulation of total and speciﬁc IgE serum levels to a panel of molecular house dust mites (HDM) and storage mites (SM) allergens in patients with severe AD. Methods: Demographic and clinical data for severe AD adult patients receiving dupilumab (300mg every 4 weeks) were reviewed. Mean values and percent changes from baseline in total and sIgE to the HDM and SM extracts, and 14 individual molecular allergens were measured over 52 weeks. Results: Significant changes in mean total IgE levels were observed from baseline to week-52 after treatment with dupilumab. Despite no changes were found in sIgE against the complete extract of HDM during the 52-week treatment with dupilumab, baseline mean levels from 7 of 14 individual molecular mite allergens -Der p 1, Der p 2, Der p 5, Der p 7, Der p 21, Der p 23 and Lep d 2- were significantly decreased after 52 weeks of treatment with dupilumab. Conclusions: Dupilumab therapy for 52 weeks resulted in a profound reduction in blood levels of total IgE and allergen-speciﬁc IgE to both HDM and SM at the molecular level in adults with severe AD under RWE conditions. The potential benefits of these concomitant immunomodulatory effects after treatment with dupilumab should be explored to a greater extent.